2013
DOI: 10.1128/iai.00186-12
|View full text |Cite
|
Sign up to set email alerts
|

MAPK-Activated Protein Kinase 2 Contributes to Clostridium difficile-Associated Inflammation

Abstract: Clostridium difficile infection (CDI) results in toxin-induced epithelial injury and marked intestinal inflammation. Fecal markers of intestinal inflammation correlate with CDI disease severity, but regulation of the inflammatory response is poorly understood. Previous studies demonstrated that C. difficile toxin TcdA activates p38 kinase in tissue culture cells and mouse ilium, resulting in interleukin-8 (IL-8) release. Here, we investigated the role of phosphorylated mitogen-activated protein kinase (MAPK)-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 70 publications
(88 reference statements)
2
43
0
Order By: Relevance
“…In vitro studies have implicated p38 in C difficile infection pathophysiology, 37, 38 and we recently reported that the p38 pathway and its downstream kinase target MK2 are major components of the inflammatory response elicited by C. difficile toxins in cells, mice and adults. 19 We now complement these experimental and adult data by showing that p38 is activated in children with C difficile infection. Unfortunately, pp38 is not a sensitive biomarker, and is only elevated in a subset of children with C. difficile .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In vitro studies have implicated p38 in C difficile infection pathophysiology, 37, 38 and we recently reported that the p38 pathway and its downstream kinase target MK2 are major components of the inflammatory response elicited by C. difficile toxins in cells, mice and adults. 19 We now complement these experimental and adult data by showing that p38 is activated in children with C difficile infection. Unfortunately, pp38 is not a sensitive biomarker, and is only elevated in a subset of children with C. difficile .…”
Section: Discussionmentioning
confidence: 72%
“…18 In vitro , C. difficile toxins activate the p38 pathway 19 and induce multiple pro-inflammatory cytokines and chemokines such as interleukin (IL)-8, IL-12, IL-18 and tumor necrosis factor (TNF)-α which may be responsible for host damage and many of the histopathologic features of severe illness. 18 …”
mentioning
confidence: 99%
“…Thus, exposure of intestinal epithelial cells to toxin A leads to secretion of the potent neutrophil chemoattractant interleukin (IL)-8. 57,[70][71][72] Monocytes also express IL-8, and other cytokines, in response to toxins A and B. 65,73,74 The inflammasome is a proteolytic complex that responds to signals from bacterial pathogens and from stressed host cells.…”
Section: Innate Immune Responsesmentioning
confidence: 99%
“…In particular, p38 MAPK phosphorylation has been shown to be essential for NFκB activation in response to TcdA, and this is thought to occur as a result of mitochondrial oxygen radical generation [21-22]. Both toxins have also been shown to activate MAPK-activated protein kinase (MK2) downstream of p38 MAPK, and this pathway is essential for IL-8 expression [23]. Similarly, production of cyclooxygenase-2 (COX-2) and prostaglandin E 2 (PEG 2 ), thought to be responsible for the fluid accumulation seen in response to toxins, is also dependent on p38 MAPK activation and signaling via mitogen- and stress-activated protein kinase (MSK-1) [24].…”
Section: Inflammatory Response To Toxins a And Bmentioning
confidence: 99%